2021
DOI: 10.1021/acs.joc.1c01713
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Synthesis of 1,3-Disubstituted Naphthalenes via TfOH-Promoted Directed-Aldol and Friedel–Crafts Reactions

Abstract: A TfOH-promoted tandem synthesis of 1,3-disubstituted naphthalenes is developed via a directed-aldol reaction and a Friedel–Crafts reaction. Two new C–C bonds and one new benzene ring are created efficiently in one pot due to the discovery of a TfOH-promoted highly chemoselective directed-aldol reaction between two different ketones with α-hydrogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…A wide range of aryl substituents (R) at the terminal of alkynes were first investigated, and it was found that both electron-donating groups (e.g., methyl, ethyl, methoxy, and phenyl) and electron-withdrawing substituents (e.g., fluorine, chlorine, and bromine) in different positions of the benzene ring were well tolerated in this reaction without much difference in regioselectivity and reactivity, and the desired polysubstituted naphthalenes 2b−2l were obtained in 71−93% yields. These results are comparable with those reported for the tandem reactions promoted by employing 3 equiv of TfOH as an initiator in toluene at 80 °C for 4 h via a directed-aldol reaction and a Friedel−Crafts reaction, 13 in that the corresponding 1-methyl-3-aryl-naphthalenes 2a, 2b, and 2k, were obtained in 77, 71, and 68% yields, respectively. Subsequently, it was found that substrates with heteroaryl, such as 2-thienyl and 3-thienyl, and naphthyl groups attached to the alkynyl moiety could also deliver the corresponding products 2m-2o in moderate to excellent yields.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…A wide range of aryl substituents (R) at the terminal of alkynes were first investigated, and it was found that both electron-donating groups (e.g., methyl, ethyl, methoxy, and phenyl) and electron-withdrawing substituents (e.g., fluorine, chlorine, and bromine) in different positions of the benzene ring were well tolerated in this reaction without much difference in regioselectivity and reactivity, and the desired polysubstituted naphthalenes 2b−2l were obtained in 71−93% yields. These results are comparable with those reported for the tandem reactions promoted by employing 3 equiv of TfOH as an initiator in toluene at 80 °C for 4 h via a directed-aldol reaction and a Friedel−Crafts reaction, 13 in that the corresponding 1-methyl-3-aryl-naphthalenes 2a, 2b, and 2k, were obtained in 77, 71, and 68% yields, respectively. Subsequently, it was found that substrates with heteroaryl, such as 2-thienyl and 3-thienyl, and naphthyl groups attached to the alkynyl moiety could also deliver the corresponding products 2m-2o in moderate to excellent yields.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…Additionally, compared with transition metal catalysts, trifluoromethanesulfonic acid (TfOH) is stable, accessible, and operational and has been regarded as a useful catalyst in synthetic chemistry to construct various compounds . Fortunately, we have successfully developed the TfOH-catalyzed cascade C–H/N–H annulation of indole-2-carboxamides with benzoquinones for the construction of indolo­[2,3- c ]­quinolinones with good chemo-/regioselectivity under the mild conditions (Scheme e).…”
Section: Introductionmentioning
confidence: 73%
“…Scheme 93 Naphthalene substrates synthesized by reaction of phenylacetaldehydes and 2-alk-1-ynylbenzyl alcohols Also in 2021, Wang, Hu, and co-workers reported the aldol and Friedel-Crafts reactions between 1,2-diarylethanone 651 and acetophenone 652 in the presence of triflic acid catalyst in toluene at 80 °C for 4 h to give 1,3-disubstituted naphthalenes 653 (Scheme 94). 110 Ketones and ary-lacetaldehyde substituted with NO 2 (654), CF 3 (655), Me (659), OMe (658), and Br (656) all gave 1,3-disubstituted naphthalenes in good to excellent yield. Mechanistically, initial formation of an enol intermediate in the presence of triflic acid is followed by aldol reaction with the ,-unsaturated ketone, resulting in the formation of a stilbene intermediate.…”
Section: Review Synthesismentioning
confidence: 99%